Learn AWS serverless computing : a beginner's guide to using AWS Lambda, Amazon API Gateway, and services from Amazon Web Services - Patterson, Scott (Packt Publishing, 2019)
Questions -- Further reading -- Section 2: Getting Started with AWS Lambda Functions -- Chapter 3: The Foundations of a Function in AWS -- Technical requirements -- Learning about AWS Lambda -- Fundamentals of a function -- Invoking a function -- Pricing model -- Ephemeral state -- High availability -- Service limits -- Use cases -- Setting up security -- Execution policies -- Function policies -- Invoking Lambda functions -- Invocation types -- Event sources -- Execution environment -- Environment variables -- Anatomy of a Lambda function -- Handler function